Effect of Soil Covering and Spraying with Plant Extracts on Qualitative and Quantitative Characteristics of Lycopersicon esculentum Mill Tomato - Al-Wakaa, Adnan Hussein Ali; Hammad, Hamid Saleh; Al-Mandalawi, Ahmed Amer Murad (Journal of agricultural, environmental and veterinary sciences, 2017)
A field experiment was carried out at the Experimental Station of the Department of Horticulture and Garden Engineering, Faculty of Agriculture, Diyala University, for the 2016 spring season to study the effect soil coverings (no coverage, black polyethylene coverage, white cover), plant extracts spray, and consisted of five levels control (spraying distilled water ) , spray with Blady grass, Nut grass, onion extract and Johnson grass extracts In the qualities of the quantity and quality of tomato plant, The number of fruits included, yield of one plant, Production per Kg.ha-1, Acidity of fruits, Vitamin C and Tss with fruits. The results were as follows: Soil cover treatments had a positive effect on all quantitative and qualitative characteristics and the soil coverage of polyethylene was significantly higher than the second type of cover and the comparison treatment was not covered. The spraying of the plant extracts separately resulted in a significant and significant reduction in all studied traits compared to spraying with treatment control. The spray treatment with Nut grass extract was characterized by increasing the reduction rate in the measured vegetative growth measurements from the rest of the other extracts followed by spraying with the Johnson grass extract and then spraying with the Blady grass extract and spraying with the onion extract.